Exploiting replicative stress in gynecological cancers as a therapeutic strategy. Issue 8 (22nd June 2020) - Ngoi, Natalie YL; Sundararajan, Vignesh; Tan, David SP
Abstract : Elevated levels of replicative stress in gynecological cancers arising from uncontrolled oncogenic activation, loss of key tumor suppressors, and frequent defects in the DNA repair machinery are an intrinsic vulnerability for therapeutic exploitation. The presence of replication stress activates the DNA damage response and downstream checkpoint proteins including ataxia telangiectasia and Rad3 related kinase (ATR), checkpoint kinase 1 (CHK1), and WEE1-like protein kinase (WEE1), which trigger cell cycle arrest while protecting and restoring stalled replication forks. Strategies that increase replicative stress while lowering cell cycle checkpoint thresholds may allow unrepaired DNA damage to be inappropriately carried forward in replicating cells, leading to mitotic catastrophe and cell death. Moreover, the identification of fork protection as a key mechanism of resistance to chemo- and poly (ADP-ribose) polymerase inhibitor therapy in ovarian cancer further increases the priority that should be accorded to the development of strategies targeting replicative stress. Small molecule inhibitors designed to target the DNA damage sensors, such as inhibitors of ataxia telangiectasia-mutated (ATM), ATR, CHK1 and WEE1, impair smooth cell cycle modulation and disrupt efficient DNA repair, or a combination of the above, have demonstrated interesting monotherapy and combinatorial activity, including the potential to reverse drug resistance and have entered developmental pipelines. Yet unresolved challenges lie in balancing the toxicity profile of these drugs in order to achieve a suitable therapeutic index while maintaining clinical efficacy, and selective biomarkers are urgently required. Here we describe the premise for targeting of replicative stress in gynecological cancers and discuss the clinical advancement of this strategy.